Minimal Invasive Radioguided Ectopic Parathyroidectomy in Upper Mediastinum - Koc, Zehra Pinar; Karlidag, Turgut; Kara, Pelin Ozcan; Akyigit, Abdulvahap; Dagli, Ferda (Galenos Yayincilik, 2019)
In this study we wanted to present a case with the history of multiple previous neck explorations and persisting upper mediastinal ectopic parathyroid adenoma who underwent a successful operation with radioguided minimal invasive approach.
Üst mediastinal paratiroid adenomunun gamma prob ile minimal invaziv eksizyonu
Keywords: Hyperparathyroidism; adenoma; minimally invasive; radioimmunodetection